Atomoxetine Reestablishes Long Term Potentiation in a Mouse Model of Attention Deficit/Hyperactivity Disorder - Ugarte-Martinez, G; Morales-Munoz, B; Rozas-Salas, C; Rojas-Montecinos, P; Zeise-Ssa., M; Contreras-Pacheco, D; Hardy-Traverso, P; Piña-Muñoz, R (Elsevier Ltd, 2020)
Attention deficit/hyperactivity disorder (ADHD) is the most prevalent psychiatric childhood disorder, characterized by hyperactivity, impulsivity and impaired attention, treated most frequently with methylphenidate (MPH). For children and adults with ADHD who do not respond satisfactorily or do not tolerate well stimulants such as MPH or D-Amphetamine, for them the alternative is to use Atomoxetine (ATX), a norepinephrine (NE) transporter inhibitor that increase extracellular NE. We examined the effects of ATX on behavior and hippocampal synaptic plasticity in the murine prenatal nicotine exposure (PNE) model of ADHD. ADHD symptoms were measured using behavioral tests, open field for hyperactivity and the Y-maze for spatial working memory. Further, ATX effects on long-term potentiation (LTP) in hippocampal slices at the CA3–CA1 synapse were assessed. PNE mice exhibited the behavioral deficits of ADHD, hyperactivity and spatial memory impairment. Intraperitoneal injection of ATX (2 mg/kg/day) normalized these behaviors significantly after 7 days. In PNE mice LTP was reduced (110.6 ± 4.5% %; n = 7) compared to controls (148.9 ± 5.2%; n = 7; p < 0.05). ATX administration (5 µM) reestablished the LTP in PNE mice to levels similar to the controls (157.7 ± 6.3%; n = 7). Paired-pulse ratios (PPR) were not significantly different for any condition. These results indicate that administration of ATX in a PNE model of ADHD reestablishes TBS-dependent LTP in CA3–CA1 synapses. The results suggest postsynaptic changes in synaptic plasticity as part of the mechanisms that underlie improvement of ADHD symptoms induced by ATX. © 2019 IBRO